Boyer-Moore String Matching Algorithm and SHA512 Implementation for Jpeg/exif File Fingerprint Compilation in DSA - Rachmad Fitriyanto; Anton Yudhana; Sunardi Sunardi (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2020)
The jpeg/exif is file’s format for image produced by digital camera such as in the smartphones. The security method for jpeg/exif usages in digital communication currently only full-fill prevention aspect from three aspects of information security, prevention, detection and response. Digital Signature Algorithm (DSA) is a cryptographic method that provide detection aspect of information security by using hash-value as fingerprint of digital documents. The purpose of this research is to compile jpeg/exif file data fingerprint using the hash-value from DSA. The research conducted in four stages. The first stages is the identification of jpeg/exif file structure using Boyer-Moore string matching algorithm to locate the position of file’s segments. The second stage is segment’s content acquisition. The third stage the image files modification experiments to select the suitable element of jpeg/exif file data fingerprint. The fourth stage is the compilation of hash-values to form data fingerprint. The Obtained result has shown that the jpeg/exif file fingerprint comprises three hash value from the SOI segment, APP1's segment, and the SOF0 segment. The jpeg/exif file fingerprint can use for modified image detection, include six types of image modification there are image resizing, text addition, metadata modification, image resizing, image cropping and file type conversion